"Summer Shift": A Potential Effect of Sunshine on the Time Onset of ST‐Elevation Acute Myocardial Infarction. Issue 8 (6th April 2018) - Cannistraci, Carlo Vittorio; Nieminen, Tuomo; Nishi, Masahiro; Khachigian, Levon M.; Viikilä, Juho; Laine, Mika; Cianflone, Domenico; Maseri, Attilio; Yeo, Khung Keong; Bhindi, Ravinay; Ammirati, Enrico
Abstract : Background: ST‐elevation acute myocardial infarction (STEMI) represents one of the leading causes of death. The time of STEMI onset has a circadian rhythm with a peak during diurnal hours, and the occurrence of STEMI follows a seasonal pattern with a salient peak of cases in the winter months and a marked reduction of cases in the summer months. Scholars investigated the reason behind the winter peak, suggesting that environmental and climatic factors concur in STEMI pathogenesis, but no studies have investigated whether the circadian rhythm is modified with the seasonal pattern, in particular during the summer reduction in STEMI occurrence. Methods and Results: Here, we provide a multiethnic and multination epidemiological study (from both hemispheres at different latitudes, n=2270 cases) that investigates whether the circadian variation of STEMI onset is altered in the summer season. The main finding is that the difference between numbers of diurnal (6:00 to 18:00) and nocturnal (18:00 to 6:00) STEMI is markedly decreased in the summer season, and this is a prodrome of a complex mechanism according to which the circadian rhythm of STEMI time onset seems season dependent. Conclusions: The "summer shift" of STEMI to the nocturnal interval is consistent across different populations, and the sunshine duration (a measure related to cloudiness and solar irradiance) underpins this season‐dependent circadian perturbation. Vitamin D, which in our results seems correlated with this summer shift, is also primarily regulated by the sunshine duration, and future studies should investigate their joint role in the mechanisms of STEMI etiogenesis.